Does resource availability help determine the evolutionary route to multicellularity?. Issue 3 (25th March 2019) - Hamant, Olivier; Bhat, Ramray; Nanjundiah, Vidyanand; Newman, Stuart A.
Abstract: Genetic heterogeneity and homogeneity are associated with distinct sets of adaptive advantages and bottlenecks, both in developmental biology and population genetics. Whereas populations of individuals are usually genetically heterogeneous, most multicellular metazoans are genetically homogeneous. Observing that resource scarcity fuels genetic heterogeneity in populations, we propose that monoclonal development is compatible with the resource‐rich and stable internal environments that complex multicellular bodies offer. In turn, polyclonal development persists in tumors and in certain metazoans, both exhibiting a closer dependence on external resources. This eco‐evo‐devo approach also suggests that multicellularity may originally have emerged through polyclonal development in early metazoans, because of their reduced shielding from environmental fluctuations.